Perancangan Sistem Administrasi Tugas Akhir Berbasis Website Menggunakan Metode Waterfall Pada Fakultas Ekonomi dan Bisnis Islam UIN Sumatera Utara Medan: Perancangan Sistem Administrasi Tugas Akhir Berbasis Website Menggunakan Metode Waterfall Pada Fakultas Ekonomi dan Bisnis Islam UIN Sumatera Utara Medan - Siti Aisyah; Muhammad Yafiz (Program Studi Teknik Informatika Universitas Pamulang, 2025)
The management of final projects at the Faculty of Economics and Islamic Business, State Islamic University of North Sumatra, Medan, is still carried out conventionally, namely through the collection of physical documents, manual form filling, and verification and approval processes that require students to interact directly with administrative staff. This situation causes various problems, including time inefficiency, the risk of document loss or damage, limitations in monitoring the progress of final projects, and difficulties in integrated data management and evaluation. This study aims to design a website-based final project administration system that can integrate the entire final project management process in a structured and well-documented manner. The system development method used is the Waterfall method, which includes the stages of requirements analysis, system design, coding, and testing. Data collection was conducted through interviews with students, lecturers, study programme managers, faculty academic departments, faculty leaders, and literature studies to identify the needs of system users, including students, supervisors, and study programmes. The results of the research are the design and implementation of a website-based final assignment administration system that supports title submission, guidance, proposal seminars, final hearings, assessments, and digital document archiving. System testing using the black-box testing method showed that all system functions ran according to the established requirements and specifications. Thus, the designed system is expected to improve the effectiveness, efficiency, and accuracy of final project administration management at the Faculty of Economics and Islamic Business, UIN North Sumatra, Medan.